Predictive value of coronary artery calcium score in cardiovascular disease - Shurong Liu; Xue Zheng; Jiahuan Xu; Xinhua Wang; ,Yuzhen Zhang; Bin Lv; Liang Zheng; Kai Sun (Frontiers in Bioscience-Elite, 2020)
We investigated coronary heart disease (CHD) and cardiovascular disease (CVD) event rates in a diverse population with a coronary artery calcium score (CACS) of 0 and the role of CACS in the detection of subclinical noncalcified atherosclerotic plaque. A total of 15,884 participants in five studies were included in this meta-analysis. Hazard ratios (HRs) with 95% confidence intervals (95% CIs) were calculated. The results showed that CHD incidence significantly increased with increased CACS (HR=0.05, 95% CI 0.03–0.06, Z=5.82, P=0.002). The CHD rate was low and further increased with CACS of 101–300. With CACS >300, the CHD rate was highest. Similarly, CVD rate was low with CACS of 0, increased with CACS of 1–100 (HR=0.03, 95% CI 0.01–0.06, Z=1.66, P=0.096), and further increased with CACS of 101–300. With CACS >300, the CVD rate was highest. Clinical evidence indicated that the higher the CACS, the higher the CHD and CVD rates, while the CVD rate does not always decreased compared with CHD rate with the same CACS, especially with CACS of 0.